THE ROLE OF THE AFFECTIVE DIMENSION IN SHAPING FOREIGN LANGUAGE LEARNERS’ CONCEPTUAL SYSTEM - Strugielska, Ariadna (Neofilolog, 2019)
The role of affective factors in the process of foreign language learning and teaching is undeniable. Still, despite growing interest in the role of attitudinal variables in foreign language training, the problem has not been much researched from the perspective of multidimensional cognition. Thus, the focus of the article is the architecture of foreign language learners’ cognition situated within a multimodal framework and shaped by particular socio-linguistic experience. It is postulated that the conceptual system of a foreign language learner is unique in being highly susceptible to processing in terms of affective parameters. This hypothesis is corroborated by the results of a pilot study which show that concrete words in the conceptual systems of foreign language learners are associated with affect more than in the case of native speakers.